Problems with segregation. Reflections after reading Włodzimierz Mędrzecki's 'Reclaimed Trash’ - Maciej Fic (Studia Historiae Oeconomicae)
Book Review: Włodzimierz Mędrzecki (2022) Odzyskany śmietnik. Jak radziliśmy sobie z niepodległością w II Rzeczypospolitej [Reclaimed Trash. How we coped with independence in the Second Polish Republic], Kraków: Wydawnictwo Literackie, 483 pages, ISBN 978-830-808-009-2.